Strategies for the Control of E-Cigarette Use among Undergraduate Students in Northeastern, Thailand: A Qualitative Study - Sihawong, Sirisup; Laosupap, Kitti; Meenakate, Phusanisa (Journal of health and health management, 2026)
The global consumption of e-cigarettes showed an increasing trend, particularly among young people, and had widespread impacts on health, society, the economy, and the environment. This qualitative research aimed to explore strategies for controlling e-cigarette consumption among undergraduate students. Data were collected through in-depth interviews using a semi-structured interview approach. The informants consisted of 30 undergraduate students from a higher education institution in Ubon Ratchathani Province from a wide range of disciplines, covering science and technology, social sciences, and the humanities, selected through snowball sampling. Data were analyzed using content analysis. The study revealed that the strategies for controlling e-cigarette consumption among undergraduate students consisted of (1) University policy and management, (2) Education and awareness promotion, (3) Counseling and cessation support services, (4) Student participation, and (5) Technology and innovation utilization. The findings also revealed an important new insight that undergraduate students tended to respond more positively to e-cigarette control measures that emphasized supportive approaches and creative communication rather than measures that relied solely on punitive actions. Furthermore, integrating peer involvement, digital technologies, and easily accessible counseling services enhanced the effectiveness of university policies and facilitated more sustainable behavior change. These findings suggested that e-cigarette control in university settings should be implemented through an integrated support system that balances policy enforcement, the learning environment, and active student participation. The results of this study helped universities and related agencies formulate policies and operational guidelines that aligned with the context and needs of undergraduate students, thereby contributing to the development of more appropriate and effective operational models for e-cigarette control.